The Effectiveness of Cooperative Learning Model of Auditory, Intellectual, Repetition (AIR) Type Assisted by PowerPoint Media on Class VII Quadrilateral and Triangular Material in Kamus Yapirru Tebas Islamic Junior High School - Nur Baiti Jannah Beti; Fajriyah Rachmatika (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This study describes the effectiveness of learning in the classroom using the auditory, intellectual, and repetition (AIR) cooperative learning model. This study also uses the help of PowerPoint media. This article's data presentation is part of a research report whose primary focus is observing the effectiveness of learning using the auditory, intellectual, repetition (AIR) cooperative learning model with the help of PowerPoint media. The research method uses descriptive qualitative to describe student learning outcomes, activities, and responses. Student learning outcomes are measured using learning outcomes tests and quiz question tests. Student activity data was carried out using student activity observation sheets. Student activity data was collected using student response questionnaire sheets. The subjects of this research were class VII students consisting of 24 students. Research results prove that: (1) Overall student learning outcomes meet the minimum completeness criteria (KKM), that is, all students score above the KKM. (2) Student activity is classified as active during learning. (3) Student responses are categorized as very good or positive